Brooding and neuroticism are strongly interrelated manifestations of the phenome of depression - Vasupanrajit, Asara; Maes, Michael; Jirakran, Ketsupar; Tunvirachaisakul, Chavit (Frontiers in Psychiatry, 2023)
We found that neuroticism may be identified as a subclinical manifestation of the phenome of depression, comprising depressive and anxiety symptoms, and suicidal behaviors. Rumination is positively associated with depression and neuroticism and may mediate the effects of neuroticism on depression. This study aims to determine whether rumination or its components, including brooding or reflection, mediate the effects of neuroticism on depression, or alternatively, whether both neuroticism and rumination are manifestations of the phenome of depression. This study recruited 74 depressed subjects and 44 healthy controls. The depression group was split into groups with high versus low brooding scores. We used partial least squares (PLS) to examine mediation effects. We found that brooding and reflection scores are significantly higher in depressed patients than in controls. Patients with higher brooding scores have increased severity of depression, anxiety, insomnia, neuroticism, and current suicidal ideation as compared with patients with lower brooding scores and controls. There is a strong positive association between rumination, and neuroticism, depression, anxiety, and lifetime and current suicidal behaviors. PLS analysis shows that brooding does not mediate the effects of neuroticism on the depression phenome, because no discriminant validity could be established between neuroticism and brooding, or between neuroticism and brooding and the depression phenome. We were able to extract one validated latent vector from brooding and neuroticism, insomnia, depression, anxiety, and current suicidal behaviors. Overall, this study supports the theory that rumination and neuroticism are reflective manifestations of the phenome of depression.